Islamic Community Empowerment Through the Da’wah Movement to Improve Adolescent Girls’ Compliance with Iron Supplements for Stunting Prevention in Madrasahs and Public Schools - Hasan Mukmin (Jurnal Pendidikan Islam, 2025)
Anemia in adolescent girls is a serious public health problem in Indonesia, contributing to the high prevalence of stunting. Despite widespread distribution of iron supplements, adolescent girls' compliance with iron supplements remains low. This study aims to explore how community empowerment based on Islamic values can improve adolescent girls' adherence to iron supplements as a measure to prevent stunting in madrasahs and public schools of Pringsewu Regency, Lampung, Indonesia. Data were analyzed using Miles and Huberman's interactive model and interpreted in light of Julian Rappaport's empowerment theory, which encompasses the components of trust, norms, and social networks. The study involved adolescent girls from 62 junior high schools under the authority of the Pringsewu District Education and Culture Office, as well as 43 Islamic junior and senior high schools (madrasahs). The results indicate that Islamic values play a significant role in shaping health behavior. Trust in religious leaders, internalization of Islamic health norms, and support from religious community-based social networks positively contribute to increased adherence to iron supplements. The integration of spiritual responsibility and health practices has been shown to promote higher motivation and compliance. Religion-based empowerment provides a contextual and meaningful framework for improving adolescent girls' compliance with iron supplements. These findings contribute to the notion that health education that prioritizes a contextual spiritual approach can be a relevant and sustainable strategy for preventing stunting, particularly within Islamic educational institutions.